CRISPR screening in cardiovascular research - Shan, Haihuan; Fei, Teng (Frontiers in Cell and Developmental Biology, 2023)
The recent advent and widespread application of CRISPR-based genome editing tools have revolutionized biomedical research and beyond. Taking advantage of high perturbation efficiency and scalability, CRISPR screening has been regarded as one of the most powerful technologies in functional genomics which allows investigation of different genetic subjects at a large scale in parallel. Significant progress has been made using various CRISPR screening tools especially in cancer research, however, fewer attempts and less success are reported in other contexts. In this mini-review, we discuss how CRISPR screening has been implemented to study questions in cardiovascular research and related metabolic disorders, highlight the scientific progress obtained via CRISPR screening, and further envision how to fully unleash the power of this technique to expedite scientific discoveries in these fields.